Critical Analysis of the Role of Oncology Nurses in Holistic Cancer Care - Aljohani, Fatimah Rasheed; Alenezi, Mona Mohammed Suliman; Aljohani, Melha Rasheed; Alerwi, Norah Ahmad; Almohammadi, Sahar Marzouk; Alzahrani, Mohammed Ali Ahmed; Ibrahim, Taghreed Abdulaziz; alkhusayfi, Zahrah Mohammed; Alkhusayfi, Fatimah Mohammed (Journal of Ecohumanism, 2024)
Oncology clinical nurses care for cancer clients, especially in clinical, psychosocial, and spiritual contexts. Their roles are essential to managing the myriad, often stressful and even oppressive, experiences that patients go through during the continuum of cancer disease. This paper critically examines the role of oncology nurses in providing comprehensive cancer care, focusing on their impact on patient outcomes, quality of life, and the overall health system. The following analysis, which is based on a literature and case review as well as a nursing framework, not only identifies the role and contributions of oncology nurses but also highlights their concerns in providing holistic care. Therefore, the results underscored the significance of training oncology nurses to enhance their knowledge, awareness, and practice, enhancing the quality of care they provide to cancer patients.